Geographies of Women - Nagy-Szalóki, Zsuzsanna (Hungarian Journal of English and American Studies, 2021)
Book review: Beebe, Kathryne, and Angela Davis, eds. Space, Place and Gendered Identities: Feminist History and the Spatial Turn. London: Routledge, 2015. x + 158 pages. ISBN 978-1-138-83049-3. Hb. £110.